Optimization of Household Equipment and Instrumentation in an Effort to Save Electrical Energy in a Restaurant - Pauhesti Pauhesti; Kartika Fajarwati Hartono; Harin Widiyatni; Fadliah Fadliah; Lailatul Wastiyah; Zidane Al Baywari; Naufal Rizqurahman; Rayhaan Adi Saputra (International Journal Of Community Service, 2026)
The escalating consumption of electrical energy in the residential and micro, small, and medium enterprise (MSME) sectors—particularly within culinary businesses—has emerged as a critical issue requiring immediate attention. Energy generation in Indonesia remains heavily reliant on fossil fuels, such as coal and petroleum, which significantly accelerates carbon emissions and environmental degradation. Restaurants, as prominent entities in the culinary sector, typically exhibit high electricity consumption due to the continuous operation of electronic appliances without structured energy management. This community service initiative aimed to deliver educational intervention and implement simple instrumentation to conserve electrical energy at Raja Bakso Restaurant. The execution methodology encompassed preliminary site surveys, high-load appliance identification, installation of rudimentary monitoring and control devices, energy management workshops, and post-implementation evaluation. The technical interventions included automatic digital timers, temperature sensors, and portable power monitoring meters.